Critérios para a justiciabilidade dos direitos sociais: fundamentos, exequibilidade e universalidade - MARECO, Gabriella Dinelly Rabelo (Universidade Federal do Pará, 2017)
From the assumption that all constitutional provisions present normative character, this study intends to identify the standards that can be used by interpreters in the solution of lawsuits involving constitutional social rights. The interpretive method of classical positivism, based on the idea that the legal content of a standard can be discovered with the use of semantic parameters, combined with an individualistic understanding of the demands that deal with social rights, has leaded, in Brazil, to many problems and distortions in the allocation of public resources. In this context, this dissertation presents standards capable of providing the interpreter and the judge an more appropriate way to guide the legal argumentation. Such standards will be formulated as questions and do not lend themselves to indicate the final court decision. These questions allow the judge to take into account many relevant matters, covering mainly aspects related to the legal basis of the demand, the possibility of real satisfaction of the claim and the compliance to the right of equal access to public goods. Finally, from the interpretation of some central theses of the works of Ronald Dworkin and Robert Alexy, we can observe how two different theoretical frameworks engender very distinct practical outcomes. The comparative approach, based on the review of major works of these authors, leads to the conclusion that the ideas defended by Dworkin are more satisfactory when applied to Brazilian constitutional model, as long as the necessary adjustments are made to ensure the theory´s adequacy to its particularities.